Write a rule for the nth term of the sequence 37, 32, 27, 22, . . . .
A.
an = -5n + 42
B.
an = -3n + 40
C.
an = 5n + 32
D.
an = 5n − 42

Respuesta :

Answer:

an = -5n + 42

Step-by-step explanation:

The common difference in the sequence is 5.

That is to say:

37-32 = 5

32-27= 5

27-22 = 5.

Now to prove that -5n + 42 is the rule for the nth term of that sequence, let's test run the rule.

For the 1st term

an = -5n + 42

a1 = -5 (1) + 42

= -5 + 42

= 37

For the 2nd term

2

a2 = -5(2) + 42

= -10 + 42

= 32

Hope that helped